Experimental research on vapor-injected rotary compressor through end-plate injection structure with check valve. (December 2018) - Wang, Baolong; Ding, Yunchen; Shi, Wenxing
Abstract: Rotary compressors encounter severe performance degradation under low-temperature ambient conditions, and the vapor refrigerant-injection technology is one of the methods to solve this problem. Traditional vapor injection technologies provide a limited improvement in performance for rotary compressors. A novel end-plate injection structure was put forward in previous research. In this paper, a rotary compressor prototype with this novel end-plate injection structure was introduced. The performance of the vapor-injected rotary compressor was tested experimentally and compared with the regular one without vapor injection. The results indicated that, compared to a single-stage rotary compressor, a rotary compressor with the novel end-plate injection structure can enhance the heating capacity and COP by 16.2–31.6% and 5.1–12.0%, respectively.